Comparison of Overall Immunity Levels among Workers at Grape Orchard, Rose Greenhouse, and Open-Field Onion Farm - Anju Maharjan; Ravi Gautam; JiHun Jo; Manju Acharya; DaEun Lee; Pramod Bahadur K C; Jin Gim; Sojung Sin; Hyocher Kim; ChangYul Kim; SooYeon Lee; SooJin Lee; et al. (Elsevier, 2022)
Background: Occupational hazards in crop farms vary diversely based on different field operations as soil management, harvesting processes, pesticide, or fertilizer application. We aimed at evaluating the immunological status of crop farmers, as limited systematic investigations on immune alteration involved with crop farming have been reported yet. Methods: Immunological parameters including plasma immunoglobulin level, major peripheral immune cells distribution, and level of cytokine production from activated T cell were conducted. Nineteen grape orchard, 48 onion open-field, and 21 rose greenhouse farmers were participated. Results: Significantly low proportion of natural killer (NK) cell, a core cell for innate immunity, was revealed in the grape farmers (19.8 ± 3.3%) in comparison to the onion farmers (26.4 ± 3.1%) and the rose farmers (26.9 ± 2.5%), whereas cytotoxic T lymphocyte proportion was lower in the grape and the onion farmers than the rose farmers. The proportion of NKT cell, an immune cell implicated with allergic response, was significantly higher in the grape (2.3 ± 0.3%) and the onion (1.6 ± 0.8%) farmers compared with the rose farmers (1.0 ± 0.4%). A significantly decreased interferon-gamma:interleukin-13 ratio was observed from ex vivo stimulated peripheral blood mononuclear cells of grape farmers compared with the other two groups. The grape farmers revealed the lowest levels of plasma IgG1 and IgG4, and their plasma IgE level was not significantly different from that of the onion or the rose farmers. Conclusion: Our finding suggests the high vulnerability of workplace-mediated allergic immunity in grape orchard farmers followed by open-field onion farmers and then the rose greenhouse farmers.